Efektifitas Pembelajaran Pendidikan Agama Islam Melalui E-Learning Pada Masa Pandemic Covid-19 - M. Zaidun Djaelani; Yayat Suharyat (Program Studi Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Islam 45, 2023)
This research was motivated by the conditions of the COVID-19 pandemic from 2020 to mid-2022, which required all learning activities to be carried out at each student's home. Therefore, media is needed to convey subject matter to students and be absorbed adequately, online. The method used in this study, namely: descriptive-qualitative. The findings of the study indicate that the effectiveness of Islamic religious education learning (History of Islamic Culture, Aqidah and Akhlaq, Fiqh, Arabic, Al Qur'an and Hadith) carried out by teachers in making learning effective, has been going well, but has not been achieved optimally. Factors that support the implementation of online learning or e-learning, among others: a). There is a distribution of internet quota; b). the number of applications that can be used to increase the variety of learning models; c). can use school computers; d). student motivation on various online learning applications. Meanwhile, the inhibiting factors for this online learning process are: a). networks that are less supportive in the online learning process; b). There are still students who have not fully received a package from the school in the form of a quota to be able to access the internet network; c). Some students do not have gadgets or cell phones to access the internet.